Expression and characterization of carbohydrate binding module (CBM) from vibrio cholerae non-01 sialidase in escherichia coli. - Shadariah, Mamat; Asmad, Kari; Nadiawati, Alias (2018)
A gene encoding carbohydrate binding module (CBM) from Vibrio cholerae Non-O1 sialidase has been successfully cloned in E. coli BL21 (DE3). The gene has beem screened from different bacteria includes Pseudomonas aeruginosa ATCC 27853, Bacillus cereus ATCC 14579, Staphylococcus aureus ATCC 33862, Salmonella thypii ATCC 14028 and Vibrio cholerae Non-O1. The Carbohydrate binding module (CBM) encodes 176 amino acids from an open reading frame comprising of 530 bp nucleotide sequence. The gene was successfully expressed solubly at 18˚C when induced with 1mM IPTG. Maximum expression was observed at 20 hours after post-induction time. For purification technique, an anionic denaturing detergent method was used using SDS and Sarkosyl with gradient affinity elution at different imidazole concentrations (10, 50 and 100mM). SDS-PAGE analysis showed that the purified CBM protein exhibited a single band with molecular weight of 32 kDa. Biochemical characterization of the protein displayed optimum pH at 5.5 in 100 mM citrate buffer with the highest Tm value of 45-50ºC. The protein is showed stable between pH 5.5-6.2 and able to retain its activity from 27-56 ˚C. From the study on metal ions, addition of Mn2+ and Mg2+ ions has increased the melting temperature of the protein to 59 ºC. Addition of 1% SDS and 1% Triton in the protein was also found to increase the Tm value to 58.5ºC.